GPU-based centripetal accelerated particle swarm optimization for big data optimization problems [electronic resource] - Amantay Bilash, 1984-; Siti Mariyam Shamsuddin, supervisor; Shafaatunnur Hasan, supervisor; Fakulti Komputeran (2015)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2015